PENYULUHAN TENTANG PEMBUATAN SALE PISANG DI DESA AWANG BANGKAL BARAT KECAMATAN KARANG INTAN KABUPATEN BANJAR - Ahmad Baparki; Nina Budiwati (INSPIRASI: JURNAL PENGABDIAN KEPADA MASYARAKAT, 2026)
Banana commodities in Awang Bangkal Barat Village, Karang Intan District, Banjar Regency, are widely cultivated on farmers' lands. In this area, banana plants are grown on land adjacent to the farmers' rubber plantations. The yield of banana production in Awang Bangkal Barat Village is generally sold by the community in the form of whole banana bunches, without any added value. In fact, through processing, bananas have great potential to increase farmers' income. Banana as a food source is a source of energy (carbohydrates) that can be utilized as contemporary food preparations, one example of which is processing bananas into sale pisang (banana crisps/slices). Sale pisang is a snack made from bananas mixed with wheat flour and milk. The target partner group for this community service is the Farmers' Group in Awang Bangkal Barat Village. The Farmers' Group in this area has the potential for a substantial availability of bananas. The banana commodities cultivated by the Farmers' Group in Awang Bangkal Barat Village are planted on farmers' own land. Thus far, all members of the Farmers' Group in Awang Bangkal Barat Villagehave only utilized the banana crops in the form of the fruit to be sold directly without processing.This community service was conducted at the Farmers Group in Sungai Batang Village, West Martapura District, Banjar Regency, 17 Juni 2026. The method used in this service activity was the Community Based Participatory Action Research (CBPAR) Method. The results of this service activity indicate that 100% of the members of the Farmers Group in Awang Bangkal Barat Village can practice making banana Sales independently